INTERPRETATION OF THE œSEGALARIAK SONG BY JOSU ELBERDIN BY YOSAFAT RANNU LEPONG IN THE REVIEW OF CONDUCTING TECHNIQUE - hafi hilmiah almanda (Universitas Negeri Surabaya, 2020)
A conductor in presenting music requires a concept or technique of how the music to be displayed becomes more beauthiful and lively. This research to describe the method and application of the technique of conducting the song